Optimization of maternal healthcare at the village level in reducing maternal mortality in Bali, Indonesia - Prabawa, Panca Dwi; Widnyana, I Ketut; Pandawani, Ni Putu; Maba, Wayan (Intelektual Pustaka Media Utama, 2025)
Although maternal mortality rates in Bali have declined, the achievement remains below the government’s target, highlighting the need to strengthen the role of villages as the frontline of development. This study aims to identify alternative strategies to accelerate maternal mortality reduction by examining the supply of maternal healthcare services and the demand reflected in women’s utilization of these services at the village level. Using the analytic hierarchy process (AHP) to map accessibility across villages and servqual model to evaluate women’s perceptions of maternal healthcare services provided through integrated services post (posyandu) and village health post (Poskesdes), the study reveals significant disparities in accessibility across villages, particularly in Tabanan, Bangli, and Karangasem Regencies. While overall perceptions of healthcare quality are positive, the largest and most significant service quality gaps occur in tangibility and responsiveness. Based on these findings, the study recommends prioritizing villages with limited access to maternal healthcare services by ensuring health coverage for pregnant women from low-income households and guaranteeing the availability of midwives in villages through incentive schemes, while adopting community-based approaches to effectively reach migrant populations and improve their utilization of maternal healthcare services.